Contortion, loss and moments for joy: insights into writing groups for international doctoral students. Issue 4 (19th May 2022) - Haeri Mazanderani, Fawzia; Danvers, Emily; Hinton-Smith, Tamsin; Webb, Rebecca
ABSTRACT: The idealised internationally mobile doctoral student is often presented as seamlessly transitioning across space – translating and neutralising themselves within globalised higher education. However, for those positioned as 'international', writing can be experienced as disconnecting. This paper considers the tensions of writing, as experienced by international doctoral students. It draws on 19 semi-structured interviews and a focus group with international doctoral students to explore their experiences of research writing within a writing group. These data revealed accounts of the contortions involved in continuous acts of translation and its resulting sense of 'othering' and dislocation. Alongside these revelations emerged feelings of loss in terms of perceived 'mastery' over language and the experience of the writing group as a space for both joy and vulnerability. Consequently, we argue for the importance of doctoral writing groups that subvert and reinvent dominant narratives of writing, writers and the 'international'.